Mewujudkan Pendidikan yang Memerdekakan Peserta Didik Melalui Pemikiran Ki Hadjar Dewantara - Marini, Maya; Kurnia, Mitha; A, Adian; N, Nabila; L, Linda (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The current Indonesian education system is still constrained by an approach that is too teacher-centered and a rigid curriculum, thus limiting the space for students to develop their potential optimally. Ki Hadjar Dewantara's thoughts on liberating education offer a relevant alternative, where students are given the freedom to learn according to their interests and talents, with teachers acting as facilitators. The application of this approach is expected to improve the quality of learning and produce more creative and innovative graduates. The method used in this study is a literature study by collecting data from previous research results and their relevant results. The objectives of the literature study in this study are 1) to find the problem to be studied, 2) to find information and data that are relevant to the topic to be discussed, 3) to add new knowledge from the results of the research being studied, 4) to test a basic truth of the theoretical approach in the problem being studied. While the analysis technique used is content analysis. The findings of this study confirm the effectiveness of Ki Hadjar Dewantara's thoughts in realizing student-centered education. By emphasizing the development of morals, intellect, and physical holistically, the educational approach he proposed has proven to be able to equip students with the competencies needed to face future challenges.